The Contribution of Agricultural Sector on the Economic Growth of Nigeria - Bekun, Festus Victor (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Agriculture is known as the engine and panacea for economic growth in most developing nations of the world. As once asserted by Nobel laureate in economics Gunner Myrdal “The battle for long-run economic growth is either won or lost in the agricultural sector”. Nevertheless, how this path births economic prosperity has been the subject of debates among economist and development scholars. It is on this premise that this study is based. This study empirically examines the impact of agricultural sector on the economic growth of Nigeria. The study is conducted using annual time series data running from 1981 to 2013. The study employs Johansen multivariate cointegration test and Vector Error Correction model (VECM) as the estimation techniques. The results of the study reveals that Real Gross Domestic Product (RGDP), agricultural output and oil rents have a long-run equilibrium relationship according to the Johansen Multivariate cointegration test. Whereas, the VECM result shows that the speed of adjustment of the variables towards their long-run equilibrium path was low, estimated as 10.3042%. Based on the empirical outcomes of the result obtained, the following recommendations were offered: Firstly, government and financial institutions should make credit facilities readily available to farmers with little payback. Secondly, government should promote the diversification of the Nigerian economy to other non –oil sector and more allocation in terms of budgeting to the agricultural sector. Keywords: Agriculture, Economic growth, Nigeria, Time series, Cointegration, Vector error correction model (VECM).

ÖZ: Tarım sektörü gelişmekte olan uygarlıklar için bir motor ve her derde deva olabilen bir ilaç vazifesini görmektedir. Nobel ödüllü ekonomist Gunner Myrdal‟ın da belirttiği gibi “Uzun dönemdeki ekonomik büyüme tarım sektöründeki kazanma veya kaybetmenin mücadelesidir. Yine de bu kavramların ekonomik refahı nasıl doğuracağı ekonomist ve kalkınmacıların tartışma konusudur. Çalışmamız bu öncül tartışma üzerinde yükselmektedir. Bu çalışma ampirik olarak tarım sektörünün Nijerya örneğinde ekonomik büyüme üzerindeki etkisini ölçmeyi amaçlamaktadır. Bu çalışma 1981 yılından 2013 yılına kadarki zaman serilerini veri olarak kullanmaktadır. Çalışmada Johansen çok değişkenli eş bütünleşme modeli ile vektör hata düzeltme modeli (VECM) kullanılmıştır. Çalışmanın sonuçları reel GSYİH ile tarımsal üretim ve petrol kiraları arasında uzun dönem ilişkiye Johansen eş bütünleşim modeli aracılığıyla işaret etmektedir. Halbuki vektör hata düzeltme modeline göre değişkenlerin uzun dönem dengeye uyarlama hızı düşük olarak gerçekleşmekte yüzde 10,3042 olarak karşımıza çıkmaktadır. Ampirik verilere dayanarak şu tavsiyeler önerilebilir: ilk olarak devlet ve finansal kurumlar çiftçilere düşük geri ödemeli krediler sunmalıdır. İkinci olarak da hükümet Nijerya ekonomisini çeşitlendirmeyi seçmeli, petrol harici sektörlere de öncelik tanımalı, tarım sektörüne ayırdığı bütçeyi artırıp geliştirmelidir. Anahtar sözcükler: Tarım, ekonomik büyüme, Nijerya, zaman serisi, eş bütünleşme, vektör hata düzeltme modeli (VECM)
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Co-Supervisor: Assist. Prof. Dr. Kamil Sertoğlu, Supervisor: Assoc. Prof. Dr. Sevin Uğural.
Keywords: Economics; Inflation (Finance) - Nigeria; Economic Conditions and Developmen - Nigeria; Agriculture - Economic Aspects - Nigeria; Agriculture; Economic growth; Nigeria; Time series; Cointegration; Vector error correction model (VECM)